A synthetic model for neuromuscular control. (1st January 2012) - Srinivasan, Shankar; Mital, Dinesh; Ebomoyi, William; Haque, Syed
The movements of a limb, whether of a robot or an animal, follow the same physical laws of motion and can be characterised by mathematical equations derived from Newtonian and Lagrangian mechanics. In robotics these equations are utilised to derive the control torques from the desired task-level trajectories. But as the number of degrees of freedom increases, the computations that ensue are very large and time consuming and there is a veritable bottleneck for computing the inverse dynamics in real-time. Taking into consideration the number of muscles that there are in an animal body, it is quite evident that the inverse dynamics problem as viewed from the robotics point of view would be intractable and is probably not existent. In this paper, we report the use of 'equilibrium-point hypothesis' as a plausible solution for the inverse dynamics in neuromuscular control.